Trauma-informed Consent Education: Understanding the Grey Area of Consent Through the Experiences of Youth Trauma Survivors - Jessica Wright (Atlantis)
Sexual consent education has emerged in recent years as the most popular method of preventing gender-based violence. Yet, the concept of consent used in much contemporary programming problematically oversimplifies sexual exploration and the power dynamics it is imbued with by asserting that consent is as simple as “Yes” or “No.” The messiness of sexual negotiation or the ‘grey areas’ of consent that youth may experience are left unaddressed. By examining the experiences of youth trauma survivors through a trauma-informed lens, the limits to binary consent education become clear. I draw on empirical data from nine open-ended interviews with Canadian youth trauma survivors to demonstrate how a trauma-informed lens may be implemented in consent education. I argue that educators should include understandings of consent which falls outside the Yes/No binary in order to adequately address youth survivors’ vulnerability to sexual (re)victimization. I examine how three of the psychosocial impacts of trauma, dissociation, hypersexuality, and struggles with acquiescence, refuse the binaristic model of consent and should be considered for trauma-informed consent education. While education alone cannot end rape culture, addressing the grey area of consent in consent education may help reduce preventable harm for survivors, as well as youth more broadly.